El modelo didáctico de la formación de un cuadro químico del mundo en los estudiantes. Una vía para el cambio conceptual - Ferro, V. R.; González Jonte, R. H. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
In this paper we develop a general definition of the study of Chemistry that responds to the need to form in the students a chemical picture of the world in accordance with the didactic model developed by the authors to systematize the contents in Chemistry teaching. The concept of chemical reaction is defined in a general way, pursuing the central aim of the didactic idea, and also in an operational way, in search of a practical guide to study the chemical bond. The concepts of bond, bonding energy, and others are given a systematic treatment within these ideas.